2023
DOI: 10.3390/coatings13030491
|View full text |Cite
|
Sign up to set email alerts
|

Yttria-Doped Ceria Surface Modification Layer via Atomic Layer Deposition for Low-Temperature Solid Oxide Fuel Cells

Abstract: Atomic layer deposition (ALD) is performed to obtain less than 1 nm thick yttria-doped ceria (YDC) layers as cathode functional layers to increase the surface oxygen incorporation rate for low-temperature solid oxide fuel cells (LT-SOFCs). Introducing a YDC surface modification layer (SML) has revealed that the optimized yttria concentration in YDC can catalyze surface oxygen exchange kinetics at the interface between the electrolyte and cathode. The YDC SML-containing fuel cell performs 1.5 times better than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It was shown that, despite the lower deposition rate of ALD, the final quality obtained for the ALDdeposited layer was higher than the films deposited by sputtering, where a 30 times higher ionic conductivity was reported for ALD GDC [353]. Other ceria-doped composites such as yttria-doped ceria (YDC) have also been processed by ALD for SOFC application [354]. Balle et al studied the properties of ALD YDC while changing the Y content in a 10-20% range.…”
Section: Atomic Layer Deposition (Ald) Processmentioning
confidence: 99%
“…It was shown that, despite the lower deposition rate of ALD, the final quality obtained for the ALDdeposited layer was higher than the films deposited by sputtering, where a 30 times higher ionic conductivity was reported for ALD GDC [353]. Other ceria-doped composites such as yttria-doped ceria (YDC) have also been processed by ALD for SOFC application [354]. Balle et al studied the properties of ALD YDC while changing the Y content in a 10-20% range.…”
Section: Atomic Layer Deposition (Ald) Processmentioning
confidence: 99%